ChemInform Abstract: In situ Generated Hypoiodite Activator for the C2 Sulfonylation of Heteroaromatic N‐Oxides. Issue 45 (October 2016) - Su, Yuan; Zhou, Xuejun; He, Chunlian; Zhang, Wei; Ling, Xiao; Xiao, Xia
Abstract: A novel NaI/tert‐butyl hydroperoxide‐mediated direct α‐sulfonylation of heteroaromatic N‐oxides with sulfonyl hydrazides is described.